Invisibility and power in the digital age: issues for feminist and queer narratology. Issue 6 (3rd July 2018) - Young, Tory
ABSTRACT: This essay examines the continued assumption that representational visibility equates to power, in the digital age. It considers the tension between the image as a form that captures what already exists and the image as a future possibility in the era of the mantra 'You cannot be what you cannot see' and growing recognition of gender fluidity. After re-examination of Peggy Phelan's reminder about the power of the unmarked, I turn to Ali Smith's 2014 How to be both, a novel with an interchangeable Renaissance narrative and contemporary story in a palimpsestic structure, to propose a formula that could be described as the becoming-simultaneous of narrative sequence . In conceiving the 'unnarrated' as both a gap in what was represented in retrospect in an existing storyworld but equally as a narrative future, I link the unmarked to political possibility, and conclude that you cannot always see what you can be.